Sternodea arcana, new species (Coleoptera: Cryptophagidae: Caenoscelini): part of the Nearctic fauna? - Leschen, Richard A.b.; Gimmel, Matthew L. (Zootaxa, 2023)
The leaf litter-inhabiting genus Sternodea Reitter (Cryptophagidae: Cryptophaginae: Caenoscelini) presently contains seven Palearctic species and up to 27 undescribed species from North and Central America. Here we describe Sternodea arcana, new species, ostensibly from Florida but possibly mislabeled, and likely originating from Mexico or Central America. Consequently, the existence of Sternodea among the North American cryptophagid fauna is unknown.